Sepulturas escavadas na rocha do Norte de Portugal e do Vale do Douro: primeiros resultados do projecto SER-NPVD - Barroca, Mário (2020)
In this text, we present the preliminary results of the project "Rock-cut graves from Northern Portugal and the Douro Valley (SER-NPVD)", a project that intends to systematize the information about the rock graves in the North of Portugal, covering both banks of the Douro valley and the entire territory located north of this river. We also present an outline of the identified sites and correlated graves, approaching their main features and the type of funerary space in which they are inserted. Furthermore, we propose a first insight focused both on the integration of these monuments in the landscape, and on their relation with some of the structuring patterns of settlement.